Therapeutic application of extracellular vesicles in kidney disease: promises and challenges - Lv, Lin‐Li; Wu, Wei‐Jun; Feng, Ye; Li, Zuo‐Lin; Tang, Tao‐Tao; Liu, Bi‐Cheng (Journal of cellular and molecular medicine, 2018)
Extracellular vesicles (EVs) are nanosized, membrane‐bound vesicles released from different cells. Recent studies have revealed that EVs may participate in renal tissue damage and regeneration through mediating inter‐nephron communication. Thus, the potential use of EVs as therapeutic vector has gained considerable interest. In this review, we will discuss the basic characteristics of EVs and its role in nephron cellular communication. Then, the application of EVs as therapeutic vector based on its natural content or as carriers of drug, in acute and chronic kidney injury, was discussed. Finally, perspectives and challenges of EVs in therapy of kidney disease were described.